Analysis and keys for the teaching of Imre Kemecsey's technical model - Prendes Garcia-Barrosa, C. M.; Isorna Folgar, M. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
The price for reaching the significant results in sports implies the interaction of various factors and dimensions of sports performance. According to Malina and Bouchard (1981), among others, we should mention genetic factors, which among other aspects determine: a) Characteristics of personality associated with the competitive capacity of the person, or the emotional control